Ethical and research governance approval across Europe: Experiences from three European palliative care studies. (June 2020) - Preston, Nancy; van Delden, Johannes JM; Ingravallo, Francesca; Hughes, Sean; Hasselaar, Jeroen; van der Heide, Agnes; Van den Block, Lieve; Dunleavy, Lesley; Groot, Marieke; Csikos, Agnes; Payne, Sheila
Background: Research requires high-quality ethical and governance scrutiny and approval. However, when research is conducted across different countries, this can cause challenges due to the differing ethico-legal framework requirements of ethical boards. There is no specific guidance for research which does not involve non-medicinal products. Aim: To describe and address differences in ethical and research governance procedures applied by research ethics committees for non-pharmaceutical palliative care studies including adult participants in collaborative European studies. Design: An online survey analysed using descriptive statistics. Setting/participants: Eighteen principal investigators in 11 countries conducting one of three European-funded studies. Results: There was variation in practice including whether ethical approval was required. The time to gain full approvals differed with the United Kingdom having governance procedures that took the longest time. Written consent was not required in all countries nor were data safety monitoring committees for trials. There were additional differences in relation to other data management issues. Conclusion: Researchers need to take the differences in research approval procedures into account when planning studies. Future research is needed to establish European-wide recommendations for policy and practice that dovetail ethical procedures and enhance transnational research collaborations.